PERBANDINGAN BAKTERI ASAM LAKTAT YOGHURT SINGLE DAN DOUBLE STRAIN DALAM MENGHAMBAT PERTUMBUHAN Shigella dysenteriae - Bella Khoirunisa Prihandini; Anriani Puspita Karunia Ning Widhi; Nendyah Roestijawati (Mandala Of Health, 2023)
Dysentery is an infectious intestinal disease characterized by the appearance of blood in the stool. One of the prevention efforts is consuming fermented milk as yogurt. Yoghurt is a fermented milk using lactic acid bacteria (LAB). LAB used as single strains of Streptococcus thermophilus, Lactobacillus bulgaricus, and double strains of S. thermophilus and L. bulgaricus. The purpose of this study was to determine the ratio of LAB of single strain and double strain yoghurt in inhibiting the growth of Shigella dysenteriae by calculating the inhibition zone formed. This research used experimental design method with postest only with control group design. This study uses well diffusion. The total sample was 15, divided into 5 groups with 0%, 20%, 40%, 60%, dan 80% concentration respectively as controls. The experimental design in this study used the Completely Randomized Design (CRD) method. Data analysis used Kruskal Wallis test and Mann Whitney Post Hoc test. The results show that the average diameter of the LAB inhibition zone for double strains of S. thermophilus and L. bulgaricus > single strain L. blugaricus > S. thermophilus. In the Kruskal Wallis test, the p value was obtained = 0.002, it was found that the difference between the treated and untreated groups was obtained. The test results found a significant difference in the median inhibition zone diameter between groups. The conclusion of this study shows that the LAB double strains of S. thermophilus and L. bulgaricus are better at inhibiting growth S. dysenteriae compared to LAB single strains of L. bulgaricus or S. thermophilus yoghurt.